Perspektive obnove slovenskih gozdov v času podnebnih in družbenih sprememb - Rantaša, Boris (Gozdarski vestnik, 2023)
Sustainable, close to nature and multifunctional management of Slovenian forests ensured conserved biodiversity, conserved adaptational potential, and high mean increment and growing stock. To ensure forest functions sustainably, adaptation to the changing climate and social conditions will be necessary. The main measure of adapting the forests to climate changes is increasing diversity, including genetic diversity. Importance of the conservation of forest genetic resources and forest regeneration and tending is identified and incorporated in all regional strategic, legislative, and operational documents on the national and European level. Forest management will have to be enhanced with measures incorporating active approach to forest regeneration and tending with a wide assortment of species-wise and genetically diverse seedlings of forest tree species. In the period 2023 – 2026, around 5 million Euro of public funds will be potentially allocated for forest regeneration and seed and tree nursery activity annually. To carry out forest regeneration and tending, it will be necessary to ensure stable and flexible financing for providing forest reproductive material, executing forest regeneration, and forest nursery development. The authors also emphasize the importance of cooperation and joint performance of diverse stakeholders in the entire chain of forest reproductive material.
Keywords: climate change; družbene spremembe; finance; forest restoration; legislation; obnova gozdov; podnebne spremembe; Slovenia; Slovenija; social changes; strategije; strategy; zakonodaja